2020
DOI: 10.1111/ajt.15798
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human use of a marine oxygen carrier (M101) for organ preservation: A safety and proof-of-principle study

Abstract: Funding information French Ministry of HealthThe medical device M101 is an extracellular hemoglobin featuring high oxygen-carrying capabilities. Preclinical studies demonstrated its safety as an additive to organ preservation solutions and its beneficial effect on ischemia/reperfusion injuries.OXYgen carrier for Organ Preservation (OXYOP) is a multicenter open-label study evaluating for the first time the safety of M101 added (1 g/L) to the preservation solution of one of two kidneys from the same donor. All a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 31 publications
2
50
0
4
Order By: Relevance
“…However, in the field of kidney transplantation, a medico-economic study (called OXYOP2) is currently comparing the costs of kidney transplantation depending on whether the graft is HOPE or SCS+M101 preserved. This study is the continuation of the OXYOP trial, 17 which showed that the rate of patients necessitating at least one post-transplant dialysis was significantly lower in SCS+M101preserved kidneys compared with HOPE-preserved kidneys (7% vs. 26%, p = 0.038). As a comparison to this 19% difference in delayed graft function (DGF) rates, an international randomised, controlled trial, comparing HOPE or SCS in deceased-donor kidney transplantation 29 reported DGF rates of 20.8% and 26.5% in SCS and HOPE groups, respectively.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, in the field of kidney transplantation, a medico-economic study (called OXYOP2) is currently comparing the costs of kidney transplantation depending on whether the graft is HOPE or SCS+M101 preserved. This study is the continuation of the OXYOP trial, 17 which showed that the rate of patients necessitating at least one post-transplant dialysis was significantly lower in SCS+M101preserved kidneys compared with HOPE-preserved kidneys (7% vs. 26%, p = 0.038). As a comparison to this 19% difference in delayed graft function (DGF) rates, an international randomised, controlled trial, comparing HOPE or SCS in deceased-donor kidney transplantation 29 reported DGF rates of 20.8% and 26.5% in SCS and HOPE groups, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…[13][14][15][16] Recently, in a French clinical trial using kidney transplantation from deceased donors, M101 demonstrated safety and efficacy, drastically decreasing the rate of delayed graft function recovery from 26% to 7%. 17 However, M101 performance in cold-stored liver graft remains to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, first M101 use in human clinical trial demonstrated that kidney preservation with M101 solution (1 g/L) before transplantation, improved graft survival and renal function. No immunological/ allergic reactions or infections were reported confirming its absence of cytotoxicity and immunogenicity 38 . This study establishes the cytocompatibility of M101 (1 g/L) in EC as they represent the first line of defense in the periodontium against any foreign aggression 12 .…”
Section: Discussionmentioning
confidence: 90%
“…S1-S3). The selected concentration used in this study (1 g/L) has already demonstrated positive outcomes in vivo and in clinical trials 33,38 .…”
Section: Discussionmentioning
confidence: 99%
“…This molecule has been administered on human for transplantation as an additive in conservative solution [9] , but never directly intravenously (IV), this study revealed the safety of this product considered as a medical device of class III. However, several published preclinical data showed an effective way to transfer oxygen to hypoxia, in particular to the brain, in a study published in the journal of Neurotrauma by the Naval Medical Research Centers on Trauma brain injury animal model.…”
Section: The Hypothesismentioning
confidence: 89%